Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/09273970802020243
|View full text |Cite
|
Sign up to set email alerts
|

Orthoptic Findings and Asthenopia in a Population of Swedish Schoolchildren Aged 6 to 16 Years

Abstract: Asthenopia was significantly associated with uncorrected visual acuity < or = 0.65 and with myopia (spherical equivalent -0.50 D or less) among Swedish schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
68
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 29 publications
4
68
3
Order By: Relevance
“…Studies have found that more than 20% of schoolchildren report asthenopia including headache (Abdi et al. ; Vilela et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have found that more than 20% of schoolchildren report asthenopia including headache (Abdi et al. ; Vilela et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence supporting uncorrected moderate hypermetropia as a cause of asthenopia is sparse and equivocal, although some studies have found a higher degree of asthenopia among moderately hypermetropic children compared to emmetropic children (Abdi & Rydberg ; Abdi et al. ; Ip et al. ; Junghans et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uncorrected refractive errors cause asthenopic symptoms such as eye fatigue, pain, and headache on the frontal region. [1][2][3] The number of people who apply to a physician with these complaints is quite high.…”
Section: Introductionmentioning
confidence: 99%